2016
DOI: 10.1002/tcr.201600077
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Dynamics and Electronic Effects of Hydrogen on Solid Surfaces

Abstract: Hydrogen is involved in a variety of chemical processes on surfaces. While hydrogen exhibits vibrational and rotational dynamics in its adsorption state, it in some cases undergoes diffusion into the substrate as well as on the surface, and participates in chemical reactions. Furthermore, hydrogen exchanges an electron with surfaces having a significant effect on the surface electronic structure. In this personal account, we review our recent studies on surface nuclear dynamics of hydrogen, hydrogen transport … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 96 publications
(155 reference statements)
0
5
0
Order By: Relevance
“…NRA via the resonant 1 H­( 15 N,αγ) 12 C nuclear reaction ( 15 N + 1 H → 12 C + α + γ) was used to analyze the H depth distribution in the H 2 -exposed thin ceria films, using monochromatized 15 N 2+ ion beams of 20–40 nA near the narrow (1.8 keV) reaction resonance energy, E R = 6.385 MeV. The method is described in detail elsewhere. , Briefly, the γ-ray yield emitted in the nuclear reaction normalized to the number of incident 15 N ions quantitatively determines the density of 1 H nuclei in the sample. The 15 N ion current is measured with a Faraday cup on the beamline and the γ-detection efficiency was calibrated with Kapton ((C 22 H 10 O 5 N 2 ) n ) foil as a H concentration standard.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…NRA via the resonant 1 H­( 15 N,αγ) 12 C nuclear reaction ( 15 N + 1 H → 12 C + α + γ) was used to analyze the H depth distribution in the H 2 -exposed thin ceria films, using monochromatized 15 N 2+ ion beams of 20–40 nA near the narrow (1.8 keV) reaction resonance energy, E R = 6.385 MeV. The method is described in detail elsewhere. , Briefly, the γ-ray yield emitted in the nuclear reaction normalized to the number of incident 15 N ions quantitatively determines the density of 1 H nuclei in the sample. The 15 N ion current is measured with a Faraday cup on the beamline and the γ-detection efficiency was calibrated with Kapton ((C 22 H 10 O 5 N 2 ) n ) foil as a H concentration standard.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Research into the adsorption and desorption of hydrogen at metal surfaces has made significant progress, and the corresponding physical mechanisms for these processes have been established [7][8][9][10][11]. However, the behavior of hydrogen at the subsurface sites is still poorly understood [12]. Moreover, the atomic-level hydrogen absorption mechanism has not been established yet, and scientists have been debating between the penetration mechanisms, quantum tunneling, or a multi-atomic concerted process [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, the behavior of hydrogen at the subsurface sites is still poorly understood [12]. Moreover, the atomic-level hydrogen absorption mechanism has not been established yet, and scientists have been debating between the penetration mechanisms, quantum tunneling, or a multi-atomic concerted process [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found both experimentally and computationally that hydrogen adsorption can induce surface metallization of insulators and semiconductors. , This has been first shown for SiC and ZnO . Then, in 2009, Duan and workers predicted that hydrogen adsorption could induce surface metallicity on SrTiO 3 (001) from the first-principles density functional theory (DFT), which was subsequently confirmed experimentally by D’angelo et al , This phenomenon has also been found later on BaTiO 3 .…”
Section: Introductionmentioning
confidence: 94%